Professional Communication in Digitalized Translation Practice - Oana Celia GHEORGHIU (ACROSS)
This paper is intended as a brief overview of the most recent challenges in teaching translation, from the perspective of the ever-increasing need for professional communication in this field in a digitalized environment seen both as a workplace and a place of business. The paper advocates the introduction of the interpersonal, intercultural, communicational, and negotiating skills in parallel with the teaching of translation as a purely linguistic matter and with introducing the more technical aspects of the profession, such as CAT tools, terminological database search or compiling, machine translation, etc.